Correlation of Prostate Volume and Intravesical Protrusion of Prostate with Uroflowmetry in Evaluation of Benign Prostatic Hyperplasia - Enamullah, CA HM; Akhter, Shamima; Sikder, Abid; Jesmin, Fatema; Ahsan, Md Shafiqul; Ferdoucy, Sultana Amena (Journal of Dhaka National Medical College & Hospital, 2015)
Background: Uroflowmetry is considered as the best available noninvasive reference test to diagnose bladder outlet obstruction (BOO) due to Benign Prostatic Hyperplasia (BPH). Objective: The present study was aim to evaluate the diagnostic usefulness of ultrasonography in patients of Benign prostatic hyperplasia (BPH). Materials and Methods: This cross sectional study was carried out in the Department of Radiology & Imaging and Department of Urology at Sir Salimullah Medical College and Mitford Hospital, Dhaka from July 2009 to June 2010 conducted on elderly patients presented with Lower Urinary Tract Symptoms (LUTS) suggestive of Benign Prostatic Hyperplasia. International prostate symptoms score (IPSS), Digital rectal examination (DRE), Uroflowmetry (Qmax), serum prostate specific antigen (PSA) measurements and transabdominal ultrasound scan were performed to evaluate this study. Results: A total number of 50 elderly men were recruited in this study with a mean age of 62.14±9.98 years. High degree of negative correlation between the Qmax and prostate volume (PV) was found (r = -0.656; p = 0.001). High degree of negative correlation between the Qmax and intravesical prostatic protrusion (IPP) was found (r = -0.748; p=0.001). Conclusion: The role of sonography in the evaluation of patients with BPH is found significant as prostate volume (PV) &intravesical prostatic protrusion (IPP) correlates well with Qmax J.Dhaka National Med. Coll. Hos. 2015; 21 (02): 30-34